KARAKTERISASI TEPUNG JAGUNG DARI TIGA VARIETAS JAGUNG HIBRIDA DENGAN VARIASI LAMA PERENDAMAN - Alfina Handayani; Eny Hari Widowati; Sriyanto Sriyanto; Mursid Zuhri; Haryanto Haryanto (JURNAL LITBANG PROVINSI JAWA TENGAH, 2015)
This study aim to characterize three varieties of hybrid corn (Bisi, Pioneer 21, Pioneer 27), the appropriate method of soaking time (0, 1 and 2 hours)and the interaction of these two treatments in order to obtain the best physical and chemical properties. The method used Random Completely Design with two factors, factor I: three varieties of hybrid corn, factor II: the appropriate method of soaking time. Data was Analyzed statistically by ANOVA. The results concluded that: Variety Pioner 27 has a superior flour parameter compared with Bisi and Pioner 21, these parameter seen from the rendement, moisture content, crude fiber content. two hours soaking time had significant effect on rendement, moisture content, crude fiber, protein and carbohydrate levels, meanwhile ash and fat levels had no significant effect.